Maternal education and children's well-being: Evidence from four Pacific countries - Joseph Marshan; Dyah Pritadrajati (Asian Development Bank Institute (ADBI), 2023)
We study the relationship between maternal education and children's well-being in four Pacific countries. We exploit the richness of the Multiple Indicator Clustering Survey (MICS) dataset to investigate this relationship and its underlying mechanisms. We find that the number of years of schooling attained by mothers is positively correlated with the likelihood of children being overweight and the Early Childhood Development Index (ECDI) score, while it is negatively associated with child stunting. These patterns are mainly driven by the Kiribati and Samoa country samples, potentially due to larger sample sizes. Further investigation reveals that the number of years of schooling attained by mothers indirectly affects these outcomes through better caring practices and the higher likelihood of enrollment in early childhood education (ECE). Meanwhile, the lower likelihood of stunting appears to be a direct effect of greater maternal education. Our findings suggest that improving access to, but not the quality of, education for women may provide limited future returns for children's well-being, and they highlight the importance of disseminating specific maternal and parenting knowledge and improving ECE access.
Keywords: I25; J1; J13; F63; 330; maternal education; stunting; obesity; early childhood development; Pacific countries